2020
DOI: 10.1017/s026646742100002x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf and root attributes as growth and phosphorus uptake determinants in two grass species from South America’s natural grasslands

Abstract: Phosphorus uptake by grass species from natural South American grasslands can change depending on root and leaf attributes capable of determining higher, or lower, relative growth rate. The aim of the current study is to investigate whether leaf and root attributes capable of determining leaf and root area production in native C4 grass species Axonopus affinis and Andropogon lateralis are related to higher relative growth rate (RGR), P uptake capacity (maximum P influx; Imax) and concentration. Species grown i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The patterns regarding the uptake and use of P by forage species in this study corroborated the grouping patterns observed by Marques et al (2020a, b). They found that some forage species of the Pampa are functionally grouped as specialists in acquiring soil P and accumulating more P in their tissues; whereas other plants are specialists in using more efficiently the P absorbed and produce more biomass per unity of P. By studying the mechanisms behind these patterns, Marques et al (2021) found that forage species from the South American native grasslands with more efficient P uptake strategies also have larger root area and length per unit of root dry matter. These forage species have a higher potential to increase growth by applying P fertilizers.…”
Section: P Uptake By Different Forage Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The patterns regarding the uptake and use of P by forage species in this study corroborated the grouping patterns observed by Marques et al (2020a, b). They found that some forage species of the Pampa are functionally grouped as specialists in acquiring soil P and accumulating more P in their tissues; whereas other plants are specialists in using more efficiently the P absorbed and produce more biomass per unity of P. By studying the mechanisms behind these patterns, Marques et al (2021) found that forage species from the South American native grasslands with more efficient P uptake strategies also have larger root area and length per unit of root dry matter. These forage species have a higher potential to increase growth by applying P fertilizers.…”
Section: P Uptake By Different Forage Speciesmentioning
confidence: 99%
“…These forage species have a higher potential to increase growth by applying P fertilizers. On the other hand, species that have more conservative strategies have thicker and denser roots (smaller root area and length per unity of root dry matter), and thus, they have a lower capacity to absorb P and to respond to increased P availability in the soil after fertilization (Marques et al, 2021).…”
Section: P Uptake By Different Forage Speciesmentioning
confidence: 99%